(untitled) (The Pakistan Development Review, 2012)
This paper analyses the effects of various economic, demographic and social factors like marriage practices, education and awareness on the beliefs and attitudes regarding women’s rights to inheritance, ownership and management of property in Pakistan. Based on a random sample of 507 families from district Lakki Marwat, a backward northern district of Pakistan, the study finds that education level of respondents, including religious education, awareness of law and formal sources of information regarding women’s rights are the main factors shaping respondents’ perceptions about women’s right to inheritance, ownership and management of property. The other factors like economic status, family demography and marriage practices appear relatively less important.